17β-Estradiol modulates huntingtin levels in rat tissues and in human neuroblastoma cell line. (February 2016) - Nuzzo, Maria Teresa; Fiocchetti, Marco; Servadio, Michela; Trezza, Viviana; Ascenzi, Paolo; Marino, Maria
Highlights: HTT is an E2-inducible protein. E2-dependent HTT up-regulation relies on ERα activities. HTT is part of the E2 signaling committed to neuronal protection against oxidative stress. Abstract: 17β-Estradiol (E2) exerts neurotrophic and neuroprotective functions in the brain. Here, E2-induced increased levels of huntingtin (HTT), a protein involved in several crucial neuronal functions is reported. E2 physiological concentrations up-regulate HTT in hippocampus and striatum of rats as well as in human neuroblastoma cells. This effect requires both nuclear and extra-nuclear estrogen receptor (ER)α activities. Intriguingly, HTT silencing completely prevents E2 protective effects against oxidative stress injury. In conclusion, these data indicate for the first time that HTT is an E2-inducible protein involved in the first steps of E2-induced signaling pathways committed to neuronal protection against oxidative stress.